ปัจจัยที่ส่งผลต่อการตัดสินใจชมคอนเสิร์ต Taylor Swift The eras tour ในประเทศสิงคโปร์ - ไทยอารี วรพรต; เมธาอัครเกียรติ รัชนิพัทธิ์; บุญมีศรีสง่า มนัสสินี; ทวีผล ระชานนท์ (เสฏฐวิทย์ปริทัศน์, 2024)
The objectives of this research article aimed to: 1) study the factors influencing the organization of the Taylor Swift The Eras Tour concert and the level of decision-making to attend the concert in Singapore, and 2) study the factors affecting the decision-making to attend the Taylor Swift The Eras Tour concert in Singapore. The sample group consisted of individuals who attended the Taylor Swift The Eras Tour concert in Singapore. A sample group of 400 individuals. Data analysis involved statistical measures such as percentages, means, standard deviations, correlation coefficients, and multiple regression analysis. The study found that (1) the factor with the highest average influence on the decision to attend the concert was the artist, followed by the performance elements, venue, and pricing, and (2) independent variables such as venue, pricing, and performance elements influenced the decision.